(untitled) (Ibrahim Cardiac Medical Journal, 2012)
Management of chronic kidney disease-mineral bone disorder (CKD-MBD) can be difficult in patients with chronic kidney disease (CKD). This review aims to explain why the control of disturbed calcium, phosphate, parathyroid hormone and vitamin D metabolism is important in CKD patients. The available means to control these parameters include diet, phosphate binders, native Vitamin D, active Vitamin D derivatives and calcimimetics. However, no single measure is not enough and concerted efforts give the best result. Ibrahim Cardiac Med J 2012; 2(2): 37-40